Think green [ green opis design - Bartlett, Gillian , 1950-; Farrow, Nick; Nicholas, Damian; Thomson, Andrew; Astro Media Pty Ltd; World Wide Entertainment (Greelong,Australia : World Wide Entertainment, 2010)
Take a look at landscaping your office.
1. Celebrity fundraiser us -- 2. Regenerating towns -- 3. Asia fashion -- 4. Canada bio fuel -- 5. Green office design -- 6. Argentina wind farm --7. Kuwait flamingos
Production Design, Astro Media Pty Ltd;production editor Andrew Thomson;written by Gillian Bartlett;produced by Andrew Thomson, Gillian Bartlett; exective producer Nick Farrow
Narration Damian Nicholas
Keywords: Green technology; Industrial design -- Environmental aspects; Offices -- Designs and plans; Sustainable design